2011
DOI: 10.1074/jbc.m111.298943
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Lineage Kinase 3 Modulates β-Catenin Signaling in Cancer Cells

Abstract: Background: ␤-Catenin mediates a wide variety of cellular processes, but the signaling pathways regulating ␤-catenin downstream events are not fully understood. The role of MLK3 in modulating ␤-catenin pathway has not been reported earlier.Results: MLK3 can induce ␤-catenin stabilization but inhibit conventional ␤-catenin/TCF transcriptional activation. Conclusion: These provide a new mechanism of regulating ␤-catenin/TCF axis. Significance: MLK3 can be targeted in regulating the growth of ␤-catenin overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Taken together, the down-regulation of DVL2, LEF1, CCND1 and c-MYC, and the up-regulation of DKK and FZD receptors suggest a role of mutant MLK3 as a molecular switch between canonic and non-canonic WNT signaling. In accordance, it was recently reported that MLK3 reduces the expression of β-catenin/TCF downstream targets by promoting the interaction between β-catenin and KLF4, a known repressor of β-catenin/TCF transcriptional activity [30]. Furthermore, in accordance with a role of PCP in colorectal cancer, FZD10 was recently demonstrated to be up-regulated in colorectal cancers and matched liver metastases, and its over-expression was associated with the activation of non-canonical WNT pathway [31,32].…”
Section: Resultssupporting
confidence: 66%
“…Taken together, the down-regulation of DVL2, LEF1, CCND1 and c-MYC, and the up-regulation of DKK and FZD receptors suggest a role of mutant MLK3 as a molecular switch between canonic and non-canonic WNT signaling. In accordance, it was recently reported that MLK3 reduces the expression of β-catenin/TCF downstream targets by promoting the interaction between β-catenin and KLF4, a known repressor of β-catenin/TCF transcriptional activity [30]. Furthermore, in accordance with a role of PCP in colorectal cancer, FZD10 was recently demonstrated to be up-regulated in colorectal cancers and matched liver metastases, and its over-expression was associated with the activation of non-canonical WNT pathway [31,32].…”
Section: Resultssupporting
confidence: 66%
“…However, very little is known about the expression and the mechanisms of MLK3 in MMs. MLK3 is promotes cell proliferation by strongly activating the extracellular regulated kinase (ERK) and β‐catenin pathways . Tumour necrosis factor (TNF) and epidermal growth factor (EGF) can stimulate MLK3 to activate multiple MAPK signalling further .…”
Section: Introductionmentioning
confidence: 99%
“…VHL physically interacts with Krüppel-like factor 4 (KLF4), a transcription factor with roles in tumorigenesis [ 8 ]. Human KLF4 induces increased mouse PAX-2 and CTNNB1 mRNA expression [ 31 ] and, importantly, KLF4 binds to CTNNB1 inhibiting WNT signaling [ 13 , 34 ]. In addition, it has been shown that gain-of-function CTNNB1 mutant protein promotes increased expression of PAX-8 mRNA in mice [ 28 ].…”
Section: Discussionmentioning
confidence: 99%